Project-Based Learning in the Independent Curriculum: Improving Secondary Students’ Mathematical Problem-Solving Skills - Fahmi Abdul Halim (LP. Ma'arif Janggan Magetan, 2025)
This study aims to examine the effectiveness of Project-Based Learning (PjBL) in the context of the Independent Curriculum to improve mathematics problem-solving skills in junior high school (SMP) students. The Independent Curriculum emphasizes independent and contextual learning, encouraging the application of methods that can develop students' critical and creative thinking skills. The research method uses a mixed-methods approach with a quasi-experimental design and qualitative deepening. A total of 70 junior high school students from two classes were selected purposively; one class as an experimental group that followed PjBL-based mathematics learning, and one control class with conventional learning methods. Quantitative data was collected through math problem-solving tests before and after the intervention, while qualitative data was obtained from classroom interviews and observations to explore student motivation and engagement. Statistical analysis showed a significant improvement in problem-solving ability in the experimental group compared to the control group. In addition, qualitative results revealed that PjBL increases students' learning motivation, active engagement, and collaborative ability in solving complex mathematical problems. This study confirms that the integration of PjBL in the Independent Curriculum is effective in improving mathematical problem-solving skills holistically. The study presents practical implications and recommendations for the development of innovative and contextual mathematics learning in secondary schools.